Expression Patterns of Glycosylation Regulators Define Tumor Microenvironment and Immunotherapy in Gastric Cancer - Li, Fang; Huang, Kaibin; Pan, Chaohu; Xiao, Yajie; Zheng, Qijun; Zhong, Keli (Frontiers in Cell and Developmental Biology, 2022)
Glycosylation (Glyc) is prevalently related to gastric cancer (GC) pathophysiology. However, studies on the relationship between glycosylation regulators and tumor microenvironment and immunotherapy of GC remain scarce. We extracted expression data of 1956 GC patients from 8 cohorts and systematically characterized the glycosylation patterns of 6 marker genes into phenotype clusters using the unsupervised clustering method. Next, we constructed an Glyc.score to quantify the glycosylation index of each GC patient. Finally, we analyzed the relationship between Glyc.score and clinical traits including molecular subtype, TME, and immunotherapy of GC. Based on prognostic glycosylation-related differentially expressed genes, we constructed the Glyc.score, and divided the samples into the high and low Glyc.score groups. The high Glyc.score group showed a poor prognosis and was validated in multiple cohorts. Functional enrichment analysis revealed that the high Glyc.score group was enriched in metabolism-related pathways. Furthermore, the high Glyc.score group was associated with the infiltration of immune cells. Importantly, the established Glyc.score would contribute to predicting the response to anti-PD-1/L1 immunotherapy. In conclusion, the Glyc.score is a potentially useful tool to predict the prognosis of GC. Comprehensive analysis of glycosylation may provide novel insights into the epigenetics of GC and improve treatment strategies.